If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*(x+2))/4 = 2*x-4 // - 2*x-4
(3*(x+2))/4-(2*x)+4 = 0
(3*(x+2))/4-2*x+4 = 0
(3*(x+2))/4+(-2*4*x)/4+(4^2)/4 = 0
3*(x+2)-2*4*x+16 = 0
6-5*x+16 = 0
22-5*x = 0
(22-5*x)/4 = 0
(22-5*x)/4 = 0 // * 4
22-5*x = 0
22-5*x = 0 // - 22
-5*x = -22 // : -5
x = -22/(-5)
x = 22/5
x = 22/5
| 12=4+u/20.48 | | 8.1=7u-3.1 | | w/5+4.1=-8.4 | | -12t^4+16t^3+3t^2= | | 4+u/3=7 | | 17=2y+5 | | 90x^3+33x^2+3x= | | 10=4+y/2 | | 10=4+y-2 | | 0=10x^2+28x-174 | | 156=-y+64 | | 60x^3+35x^2+5= | | 207-x=88 | | -w+199=147 | | w/9=-39 | | 2x^2-24x-3955977=0 | | -56=-v/6 | | 10x-10=6x-2 | | H-(41)=-6 | | -2v=-17 | | (-7x^5+12x^4+7x^3+9x)-(-3x^5-4x^4-11x^2+9x)= | | 5.12=w/2 | | u/12.8=4 | | 2x^2-10x-21000=0 | | -45+15*15= | | -45+15-15= | | 4x-9-5x-3= | | (-6)(2)(-1)(5)(-3)= | | (w-2)(4w-4)= | | 22x-12=6x-10 | | 10(3b+c-6a)-8(a-8c+9b)= | | 6y-8=4y+12 |